An investigation on the effect of crack lengths and wavelengths on the dynamic cracking behaviours of brittle materials using the improved XFEM. (January 2023) - Chen, Junwei; Zhou, Xiaoping
Highlights: The crack length rarely affects the dynamic cracking behaviours. The wavelength significantly affects the dynamic cracking behaviours. Because of the different cracking behaviours, the dynamic fracture toughness increases with the loading rate. The branching of the cracks can be validated by the cracking behaviours. Abstract: In this paper, the effects of crack lengths and wavelengths on dynamic cracking behaviours are investigated using the improved extended finite element method (XFEM), in which the absorbing boundary condition is coupled into the XFEM. Subsequently, to study the evolution of the displacement and the energy affected by the cracks, numerical tests in a plate containing a crack are conducted under dynamic loads with different wavelengths. Finally, the effects of the crack lengths and wavelengths on the dynamic cracking behaviors are investigated by analysing the evolution of the dynamic stress intensity factor and the energy release rate. The numerical results show that a sudden drop in energy can be found when the angle between the incident dynamic load and the crack varies from a vertical angle to an acute angle. Additionally, it is found that the crack length rarely affects the dynamic cracking behaviours, while the wavelength does significantly affect the dynamic cracking behaviours. When the wavelength is smaller than the critical wavelength, tensile-shear cracking behavior occurs. Otherwise, the cracking behaviour consists of a compression-shear cracking pattern and a tension-shear cracking pattern.